Effects of Liquid-to-Solid Ratio and Reaction Time on Ammonia-Sulfuric Acid Pretreatment of Achnatherum splendens - Tao, L.; Ren, J.; Liu, H.; Ni, T.R. (Asian Journal of Chemistry, 2013)
For ammonia-sulfuric acid pretreatment of Achnatherum splendens, the ground biomass was first pretreated by soaking in aqueous ammonia with 10 wt % of ammonia at 55 ºC with 12:1 of liquid-to-solid ratio (based on wt) for 36 h. Then the pretreated solids were further treated with 0.5-2 % (w/v) sulfuric acid at liquid-to-solid ratio of 8:1-15:1 (v/w) for 0.5-3 h at 100 ºC. Increasing sulfuric acid concentration and reaction time in the second stage had significant effect on hemicellulose solubilization. Increases in sulfuric acid concentration and reaction time in the second stage caused significant decrease in hemicellulose and significant increase in cellulose and lignin. However, liquid-to-solid ratio had no significant effects on hemicellulose solubilization in the second stage. Liquid-to-solid ratio had also no significant effects on the yield of hemicellulose, cellulose and lignin in the solids after sulfuric acid pretreatment in the second stage. The optimum treatment conditions of the ammonia-sulfuric acid pretreatment were: 10 wt % of ammonia, 55 ºC, 36 h of reaction time, 12:1 of liquid-to-solid ratio (based on wt) in the first stage; 1.5 % (w/v) sulfuric acid, 8:1 (v/w) of liquid-to-solid ratio, 2 h of reaction time and 100 ºC in the second stage. Under these conditions, 91.19 % hemicellulose was solubilized and the content of cellulose was increased to 75.49 %.